IMPLEMENTATION OF PAMSIMAS POLICY IN THE PERSPECTIVE OF PLANNING, IMPLEMENTATION, AND SUPERVISION IN GORONTALO DISTRICT - Aneta, Yanti (Public Policy Journal, 2022)
The purpose of this research is to describe and analyze the implementation of public policies in terms of PAMSIMAS policies in order to improve the quality of public health services in Gorontalo Regency. The success of the policies carried out through the process or stages of planning, implementation, and supervision. The research approach was carried out using qualitative research methods with data collection carried out by conducting observations, interviews, documentation, structured and group discussions. The results showed that in general health services in Gorontalo Regency had increased through policies regarding PAMSIMAS which could be said to be consistent through the stages of planning, implementation and supervision.